The influence of individual noise sensitivity on mobile phone attitudes and behavior - Worthington, Debra L. and Keaton, Shaughan and Imhof, Margarete and Välikoski, Tuula-Riitta (Mobile Media & Communication, 2016)
Research in psychoacoustics and public health reveals that individuals respond differently to noise, with some being more sensitive to noise than others. Given the prevalence of mobile technology and that noise sensitivity appears to be a relatively stable individual difference, it is possible that noise sensitivity may distinguish individual mobile phone use. This study investigates the relationship between noise sensitivity and mobile phone attitudes and behaviors. Study results suggest that noise sensitive bystanders find mobile phone conversations more annoying, that they differ in their assessment of the distraction level of ambient noise when making and receiving calls, are more likely to report mobile phones as distracting, and are more likely to seek privacy from others when receiving a call.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8yMDUwMTU3OTE1NTgxNDM1